Prussian Blue Degradation during Hydrogen Peroxide Reduction: A Scanning Electrochemical Microscopy Study on the Role of the Hydroxide Ion and Hydroxyl Radical. Issue 7 (20th June 2016) - Noël, Jean‐Marc; Médard, Jérôme; Combellas, Catherine; Kanoufi, Frédéric
Abstract: The degradation of Prussian blue (PB) during H2 O2 reduction is investigated by scanning electrochemical microscopy (SECM). Coupling SECM with optical microscopy allows quantitative assessment in situ of the effect of HO − on the dissolution of PB in lithographic experiments. The local production of HO − in the vicinity of PB is an easy way to pattern a PB layer; Such PB dissolution during H2 O2 reduction leads to the release of soluble ferrocyanide and Fe 2+ . In the presence of H2 O2, the latter initiate the Fenton reaction and the generation of highly reactive hydroxyl radicals HO . . This is revealed by the degradation of an organic layer immobilized on an ultramicroelectrode held in the vicinity of a PB layer during H2 O2 reduction. The formation of such reactive species is of great importance to further understand the possible origin of the activity loss of sensors, batteries, and photovoltaic cells when composite materials based on PB or on its derivatives are used as catalysts for H2 O2 or O2 reduction. Abstract : Blue dissolution : The dissolution of Prussian blue during H2 O2 reduction is studied by using scanning electrochemical microscopy, which allows the role of HO − in lithographic processes to be assessed quantitatively. The dissolution leads to the release of soluble Fe 2+ initiating the Fenton reaction and therefore to the production of highly reactive hydroxyl radicals (see figure).